Clinical value of induction protocol after second generation cryoballoon ablation for paroxysmal atrial fibrillation. Issue 5 (31st May 2017) - Velagić, Vedran; Ströker, Erwin; de Asmundis, Carlo; Mugnai, Giacomo; Iacopino, Saverio; de Regibus, Valentina; Abugattas, Juan-Pablo; Coutiño, Hugo-Enrique; Takarada, Ken; Choudhury, Rajin; Paparella, Gaetano; De Greef, Yves; et al.
Abstract: Aims: The predictive value of induction studies after catheter ablation for atrial fibrillation (AF) is still debatable. To date, these studies have not been implemented in patients after cryoballoon (CB) ablation. Our aim was to analyse the clinical value of AF induction in patients treated by second generation CB for paroxysmal AF. Methods and results: Seventy patients underwent at first an isoproterenol challenge after pulmonary vein (PV) isolation to assess AF induction and early PV reconnections (EPVR). Patients without EPVR were evaluated for premature atrial contraction (PAC) induction; atrial ectopy was considered frequent (PAC+) if >1/10 cycles or >6/min. After restitution of baseline heart rate, rapid atrial pacing (RAP) was performed on all patients. AF induction by isoproterenol occurred only in 3/70 (4%) patients of whom 2/3 (66%) patients with an EPVR of a triggering vein. In the 62 patients without EPVR, PAC+ occurred in 17 patients (27%). RAP could induce AF in 23/70 (33%) patients. At a mean follow-up of 13.5 months, there were 11/70 (16%) AF recurrences. There was no significant difference in the AF recurrence rate between RAP inducible vs. non-inducible patients (log-rank P  =   0.33). A 41% recurrence rate (7/17 patients) was seen in the PAC+ group with significantly different AF-free survival for PAC+ vs. PAC− patients (log rank P  < 0.0001). PAC+ was the only independent determinant to predict AF recurrence after multivariate analysis. Conclusion: PAC occurrence in response to isoproterenol could predict AF recurrence after PV isolation by CB, while RAP showed no prognostic implication.